Pembantaian dukun santet di Banyuwangi: kasus pelanggaran ham berat yang belum tuntas - Aldakhil, Muhammad Rizqy; Latifah, Hilma Nurul (Maliki Interdisciplinary Journal, 2025)
Human Rights (HAM) are natural rights that are inherent to every individual from birth, universal in nature, and cannot be revoked. One of the egregious human rights violations in Indonesia is the massacre of individuals accused of being witch doctors in Banyuwangi and its surrounding areas in 1998. This tragedy illustrates a pattern of organized violence fueled by societal beliefs in witchcraft, which were exploited by certain parties to carry out brutal actions. Thousands of individuals became victims without substantial evidence. In this context, the massacre fulfills the criteria for serious human rights violations according to Law Number 26 of 2000 regarding Human Rights Courts. This article underscores the significance of law enforcement, truth disclosure, and victim rehabilitation to ensure that similar tragedies do not recur in the future